Grading Ornamental Fish - Tina C. Crosby; Jeffrey E. Hill; Carlos V. Martinez; Craig A. Watson; Roy P. Yanong (EDIS, 2006)
FA-118, a 5-page illustrated fact sheet by Tina C. Crosby, Jeffrey E. Hill, Carlos V. Martinez, Craig A. Watson, and Roy P.E. Yanong, describes how fish can be visually inspected for quality during and after harvest. Mechanical and hand grading methods are described. Includes recommended reading, an appendix of grader providers, and a table summarizing the advantages and disadvantages of the grading methods. Published by the UF Department of Fisheries and Aquatic Sciences, November 2006.